A study on serum bilirubin levels in coronary artery disease patients - N., Jayanthi; V. S. S. R., Abhilash Kasibhatla; R., Shankar (International Journal of Advances in Medicine, 2018)
Background: The protective effect of bilirubin relates to the antioxidant property of bilirubin, which prevents lipid oxidation, especially low-density lipoprotein (LDL), and inhibits free radical-induced dam-ages. Lower serum bilirubin level has been proven to be associated with endothelium and microvascular malfunction. The aim of the present study was to assess the association between serum bilirubin levels and coronary artery disease in comparison with controls without coronary artery disease. Methods: A cross-sectional study was conducted for a period of a one year in our medical college hospital. Patients with evidence of coronary artery disease for not more than 10 years of duration confirmed by ECG, ECHO and other previous case records were taken as cases. Controls were selected matched with age, gender and other co-morbid conditions. Total of 200 subjects were included in the study with 100 cases and 100 controls. General and systemic examination was conducted on all study subjects including laboratory investigations like complete blood count, renal function test, lipid profile, viral markers such as HBsAG, HCVIgM and liver function test which includes total bilirubin, direct and indirect, liver enzymes, albumin and globulin levels. A 12 lead ECG and a transthoracic echocardiogram was performed for all patients. Results: The various liver function test parameters were compared between the cases and controls it was found that the serum bilirubin levels which includes total bilirubin, direct bilirubin and indirect bilirubin was found to be lower among the case group compared to the control group and this difference was found to be statistically significant (p <0.05). A perfect linear correlation between the ejection fraction and serum bilirubin levels, as the ejection fraction decreases the serum bilirubin levels was also decreasing. Conclusions: This study showed a significant association between the reduced serum bilirubin levels and the occurrence of CAD; therefore, bilirubin level can serve as a predictive factor, together with other influential factors for identifying a person at risk of developing coronary artery disease.